The Impact of Digital Media on EFL Learners’ Listening Skills at the University Level - Abdul Syahid,; Ulpia Rahim,; Novita Sari,; Zumiyati, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study explores the impact of digital media on the development of listening skills among university-level English as a Foreign Language (EFL) students. With the increasing popularity of digital platforms such as YouTube, podcasts, and language learning applications, students have access to authentic resources outside the classroom that can enhance their listening comprehension. This study employs a quantitative survey method to analyze the influence of digital media on listening skills, considering factors such as motivation, digital literacy, and learning preferences. The findings reveal that digital media significantly impacts listening comprehension, although certain aspects show no significant differences. This research highlights the importance of integrating digital media into the EFL curriculum to enhance listening learning. In conclusion, the use of digital media can expand access to relevant and flexible learning resources, though its challenges require careful attention.